Eduardo Santos, the Public Scene and the Conservative «Hegemony» - Vanegas Useche, Isidro (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article inquires into the public life of Eduardo Santos during the Conservative Republic. It provides details of his important role in political struggles, as well reflecting on his role as actor and witness during a period of intense change. Similarly this study reflects about the construction political representation in a period of Colombian history characterized by the appeasal of violence; a period during which the owner of El Tiempo newspaper made important contributions. Based on the conceptual history of politics, this study inquires into the importance of certain leaders in the construction of the atmosphere of political détente which characterized Colombia for several decades at the beginning of the XX century.